Comparison of amniotic fluid indices in pregnancies with breech presentation with those with cephalic presentation [Sefalik prezentasyonu olan gebelerle makat prezentasyonu olan gebelerin amniotik sivi i̇ndeksi açisindan karşilaştirilmasi] - (:unkn) unknown (My University, 2005)
OBJECTIVES: To compare the amniotic fluid index (AFI) in pregnancies with cephalic presentation to that in pregnancies with breech presentation. STUDY DESIGN: Between March 2002 and December 2003, women with a singleton pregnancy between 34 and 40 weeks of gestation were divided into two groups according to the fetal presentation determined on ultrasound examination. The first group had cephalic presentation and the second group had breech presentation. Amniotic fluid indices in each group were compared. All ultrasonographic measurements were performed by the same senior obstetric resident. RESULTS: 92 pregnant women underwent AFI assessment. 64 of them had vertex, and the remaining 28 had breech presentation. Age, parity, the gestational age at which the US was performed, fetal biometry and estimated fetal weight were comparable between groups. The mean (±SD) AFI for women who had cephalic presentation was 138.3±33.5 mm and that for those having breech presentation was 156.8±47.6 mm. The difference between the two groups was statistically significant. CONCLUSIONS: Breech presentation was associated with an increased value of amniotic fluid index.
Keywords: Amniotic Fluid Index; Fetal Presentation